La didáctica en el proceso de la lectoescritura en los estudiantes de segundo año de Educación Básica de la " Unidad Educativa Marco Aurelio Subía Batalla de Panupali". - Cepeda Perugachi, Sandra Mireya (2021)
This research addresses a problem related to identifying the problems that second-year students of Basic Education of the Marco Aurelio Subía Batalla de Panupali Educational Unit have in the literacy process. For which the general objective was proposed: To improve the literacy process, through the application of methodological strategies to achieve the objective, the following methodology was used from the quantitative qualitative approach at a quantitative level, the survey was used as a technique and the questionnaire As a qualitative data collection instrument, strengths and weaknesses were analyzed. After analyzing the results, it was concluded that teachers need to know new strategies to improve the literacy process. To meet these needs in the student, methodological strategies were created to improve the literacy process; Which was validated by three specialists, reaching the following conclusions, it can be stated that they believe it is pertinent to implement the methodological strategies since this will help students to improve the literacy process.